2021
DOI: 10.1155/2021/8840167
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Locally Delivered Melatonin as an Adjunct to Nonsurgical Therapy on GCF Antioxidant Capacity and MMP-9 in Stage II Periodontitis Patients: A Randomized Controlled Clinical Trial

Abstract: Objectives. Periodontitis is characterized by inflammatory destruction of periodontal tissue, loss of attachment, and bone resorption. The increase in reactive oxygen species (ROS) is responsible for the oxidative damage occurring in periodontal tissues. Melatonin has important immunomodulatory, anti-inflammatory, and powerful antioxidant functions. The current study was carried out to evaluate the effect of topical melatonin gel as an adjunct to nonsurgical periodontal therapy. Methods. This split-mouth rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 31 publications
4
22
0
Order By: Relevance
“…There were different kinds of studies included in this review, and twelve of them showed that when the melatonin is administered, the periodontal disease has an improvement (Cutando et al, 2013,2014,2015; Cobo‐Vázquez et al, 2014; Marawar et al, 2014; Chitsazi et al, 2017; Montero et al, 2017; El‐Sharkawy et al, 2019; Tinto et al, 2020; Bazyar et al, 2019; Zare Javid et al, 2020; Anton et al, 2021; Ahmed et al, 2021). These studies analyzed the periodontal and gingival indexes and also the pocket depth and showed positive effects in patients that received the substance, proving that melatonin is able to interfere in the inflammatory, in anti‐oxidative process and in the repair mechanism, such as in the proliferation of the fibroblasts (Gómez‐Florit et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There were different kinds of studies included in this review, and twelve of them showed that when the melatonin is administered, the periodontal disease has an improvement (Cutando et al, 2013,2014,2015; Cobo‐Vázquez et al, 2014; Marawar et al, 2014; Chitsazi et al, 2017; Montero et al, 2017; El‐Sharkawy et al, 2019; Tinto et al, 2020; Bazyar et al, 2019; Zare Javid et al, 2020; Anton et al, 2021; Ahmed et al, 2021). These studies analyzed the periodontal and gingival indexes and also the pocket depth and showed positive effects in patients that received the substance, proving that melatonin is able to interfere in the inflammatory, in anti‐oxidative process and in the repair mechanism, such as in the proliferation of the fibroblasts (Gómez‐Florit et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…There were different kinds of studies included in this review, and twelve of them showed that when the melatonin is administered, the periodontal disease has an improvement (Cutando et al, 2013(Cutando et al, ,2014(Cutando et al, ,2015Cobo-Vázquez et al, 2014;Marawar et al, 2014;Chitsazi et al, 2017;Montero et al, 2017;El-Sharkawy et al, 2019;Tinto et al, 2020;Bazyar et al, 2019;Zare Javid et al, 2020;Anton et al, 2021;Ahmed et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increasing evidence from clinical trials has proved that melatonin exhibits beneficial effects for the treatment of periodontitis. For instance, local delivery of melatonin gel as an adjunct to nonsurgical periodontal therapy (NSPT) helps to provide better clinical and radiographic outcomes [ 97 , 98 ]. Systemic administration of melatonin after one-stage full mouth NSPT results in a greater clinical attachment level (CAL) gain and probing depth (PD) reduction, with reference to NSPT with placebo treatment [ 99 , 100 ].…”
Section: Melatonin: Biological Functions and Beneficial Effects On Pe...mentioning
confidence: 99%